Atuação dos profissionais de educação física na atenção primária à saúde - Joel Carlos Valcanaia Ferreira; Joel Saraiva Ferreira (Universidade Estadual do Oeste do Paraná, 2017)
O objetivo do estudo foi analisar as características sociodemográficas e econômicas dos profissionais de Educação Física atuantes na Atenção Primária à Saúde no município de Campo Grande - MS. A distribuição dos profissionais na rede municipal de saúde foi fornecida pela Secretaria Municipal de Saúde. Para obter as informações junto aos profissionais, utilizou-se de questionário autoaplicável elaborado especificamente para o presente estudo. Os resultados indicaram que 61% dos profissionais de Educação Física com vínculo funcional com a Secretaria Municipal de Saúde Pública de Campo Grande - MS atuavam na Atenção Primária. Os profissionais são maioria do sexo masculino (54%), predominância de casados (82%), faixa etária de 30 a 39 anos (73%), renda mensal de até três salários mínimos (73%), formação em Educação Física (Licenciatura Plena) (54%), concluída há mais de 10 anos (82%), majoritariamente em instituições privadas de ensino superior (73%), concursados no serviço público (91%), com jornada de serviço semanal de 40 horas (91%), atuantes há mais de três anos da Atenção Primária à Saúde (82%). Concluiu-se que as características sociodemográficas e econômicas revelaram que os PEF detém estabilidade funcional, com experiência na área de atuação e formação condizente com o contexto de intervenção. ABSTRACT. The work of physical education professionals on primary health care. The goal of this study was to analyze the sociodemographic and economical characteristics of the physical education professionals working with Primary Health Care in the municipality of Campo Grande - MS. The data were initially collected with the management of municipal department of health, in order to identify the distribution of professionals in the municipal health network and, later, with the Primary Health Care professionals themselves. In order to obtain the information from the professionals, it was used a self-applicable questionnaire devised specifically for this study. The results showed that 61% of the physical education professionals functionally linked to the municipal department of public health of Campo Grande-MS worked with primary care, which represented a coverage of approximately 30% of supply of physical activities on that level of health care. The evaluated professionals presented a sociodemographic profile with a majority of males (54%), prevalently married (82%), in the age group between 30 and 39 years old (73%), with a monthly income of up to three minimum wages (73%), with a full licentiateship in Physical Education (54%), concluded over 10 years ago (82%), mostly in private higher education institutions (73%), with public service tender (91%), with a 40-hour workweek (91%), working with primary care for over three years (82%). It was concluded that the sociodemographic and economical characteristics showed that the Physical Education professionals have functional tenure, with experience in the area of work and training in line with the intervention context.